Evaluasi Penerapan Pembelajaran Berdiferensiasi pada Mata Pelajaran Geografi Kurikulum Merdeka di SMAN 2 Gunung Talang Kabupaten Solok - Jannah, Zah Jatul; Rahmi, Lailatur (ALSYS, 2024)
The purpose of this research is 1) To find out how the implementation of differentiated learning at SMAN 2 Gunung Talang Solok Regency. 2) To find out the obstacles experienced by teachers in the Independent Curriculum Geography subject in class X SMAN 2 Gunung Talang Solok Regency. The type of research used is descriptive qualitative research. The informants in this study were the principal, teachers and students of class X phase E. The data collection techniques used in this study were observation, interviews and documentation. Data analysis techniques in this study used the Miles and Huberman model, namely data reduction, data display and verification. The results of this study concluded that 1) The application of differentiated learning is very effective to be applied in the classroom as evidenced by the increased interest in learning and student learning outcomes and all stages in the application of differentiated learning from the pre-implementation, implementation and evaluation stages have gone well and all aspects of differentiated learning have been implemented well by geography teachers. But in its implementation there are still some things that need to be maximized again. 2) The problems encountered such as the lack of time in its implementation because each school has allocated time for each teacher and their respective subjects. So that teachers do not have enough time in implementing differentiated learning and limited resources because differentiated learning is still new in its application arises because of the independent curriculum.